The Influence of Profitability and Liquidity on the Value of Pharmaceutical Sub-Sector Manufacturing Companies for the Years 2018–2022 - Rahmayanti, Eka; Prima Jaya, Fanlia; Rezti, Rezti (PT. Hanken SUkses Jaya, 2024)
This research aims to determine the influence of Profitability and Liquidity on Company Value. The independent variables (X) studied are Profitability (X1) and Liquidity (X2) with the dependent variable (Y) being Company Value (Y).The population used in this research is companies pharmaceutical sub-sector listed on the Indonesian Stock Exchange in 2018-2022. The sample selection used a purposive sampling technique which produced results samples totaling 35 samples. The data analysis technique used in this research is multiple linear regression analysis. The tests used are normality tests, multicollinearity tests, and heteroscedasticity tests, hypothesis tests, partial tests (t), simultaneous tests (F), and coefficient of determination.Based on the test results, it was concluded that partial profitability had no significant effect on company value, partial liquidity had a significant effect on company value, and simultaneous profitability and liquidity had a significant effect on company value in pharmaceutical sub-sector manufacturing companies in 2018-2022.